íntese e caracterização de catalisadores à base de prata e prata-cobre suportados em óxido de grafeno reduzido e sua aplicação na oxidação do etileno - D’ Oliveira, Monique Ribeiro (2018)
In this work, the synthesis of reduced graphene oxide (rGO) was obtained by graphite oxidation through an improved Hummers method with the elimination of NaNO3 followed by expansion and reduction using thermal methods. This modification eliminates the evolution of toxic gases such as NO2 and N2O4. The rGO was synthesized to act as support of metals (silver and copper). The catalysts were synthesized using the wet impregnation technique. The support and catalysts were widely characterized by techniques: X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Thermogravimetric Analysis (TGA), Atomic Force Microscopy (AFM), X-Ray Photoelectron Spectroscopy (XPS), Temperature Programmed Surface Reaction (TPSR) and Diffuse Reflectance Fourier Transform Infrared Spectroscopy (DRIFTS). The results showed that the graphite oxidation and its further expansion and reduction were efficient once the rGO obtained presented few graphene layers (ranging from mono to few layers) and high specific surface area (481 m2 /g). The metals were distributed on the surface of the rGO, with silver being in its reducted form and copper in the form of oxides. The catalysts were evaluated in the partial oxidation of ethylene.